Alteration of immune profiles is associated with pulmonary function and symptoms in patients with chronic obstructive pulmonary disease - Li, Sixiang; Zhao, Shuang; Wu, Zhenru; Wang, Fangfang; Li, Weimin (Molecular medicine reports, 2021)
Inflammation serves a key role in chronic obstructive pulmonary disease (COPD). However, changes in the immune profiles of patients with COPD remain unclear. The present prospective observational study aimed to determine the expression profiles of immune cells and inflammatory factors of patients with COPD and healthy controls, and to analyze the relationship between immune profiles and smoking history. A total of 140 subjects were enrolled in the present study between September 2018 and April 2019 at West China Hospital of Sichuan University (Chengdu, China). These included 87 patients with stable COPD and 24 patients with acute exacerbated COPD, as well as 29 healthy controls. Baseline characteristics were recorded during the screening period, and levels of immune cells were examined using flow cytometry. In addition, levels of inflammatory factors were measured using ELISAs. The results revealed increased expression of the CD64 /CD14 mononuclear phagocyte system (MPS) and CD16 CD66 neutrophils, and decreased expression of CD3 CD4 T cells and CD3 CD8 T cells (all P<0.05) in the peripheral blood of patients with COPD and smokers relative to non‑smoking controls. In addition, significant differences were observed in protein levels of IL‑6, IL‑1β, TNF‑α, TGF‑α, IFN‑γ, IL‑8, IL‑17A and CRP among the three groups (all P<0.05). Furthermore, the IL‑17A, TNF and NF‑κB signaling pathways were found to serve a key role in the inflammatory network of COPD. Pearson's correlation analysis revealed a positive correlation between CD3 T lymphocyte counts and pulmonary function, and a negative correlation with smoking and exacerbations. Furthermore, neutrophils and MPS were negatively associated with pulmonary function, and IL‑8 was positively associated with cough. There was also a negative association between CRP and IL‑17A with pulmonary function but a positive correlation with symptoms and exacerbation. Club cell secretory protein was also negatively associated with emphysema parameters. In conclusion, the present findings revealed significant differences in profiles of immune factors among patients with COPD, smokers and non‑smoking controls and their association with clinical characteristics. The clinical trial registration number of the present study is: ChiCTR1800015700 (registered with http://www.chictr.org.cn/index.aspx, 2018/04/16).